MEMAHAMI KONSEP ISLAM SEBAGAI AGAMA TOLERAN - Mahfud; Patsun (CENDEKIA: Jurnal Studi Keislaman, 2019)
This paper tries to capture the current conditions in Indonesia, where there are often conflicts due to sara issues. The trigger is none other than the hoax problem. If we see an explosion of conflict that occurred lately that is sprinkled to the surface is a very sensitive issue, namely the problem of ethnicity and religious issues. In the context of nation and state, Indonesia is inhabited by a variety of tribes and religions. As Muslims, we should be able to understand more sensitively that we live in this country side by side with followers of other religions, which if we cannot understand properly, there will be greater conflict. Therefore, developing the concept of tolerance in Islam must be echoed by everyone, so that in the end there will be harmony in the nation and state.